P68 Higher generic tacrolimus dosing may be required to achieve the same level and 12-month outcomes as innovator tacrolimus in liver transplantation. (20th September 2022) - Stephenson, Barney; Rimmer, Peter; Smith, Amanda; Bartlett, Mr David; Trivedi, Palak; Rajoriya, Neil
Abstract : Generic tacrolimus has been proposed to provide cost savings over innovator tacrolimus in transplantation whilst preserving clinical outcomes. Whilst increasing evidence supports this approach for renal transplantation, there remains a paucity of published studies in the field of liver transplantation. The aim of this study was to compare the clinical outcomes of de novo generic tacrolimus (Adoport, Sandoz, UK) with innovator tacrolimus (Prograf, Astellas, Japan) in liver transplantation. A single centre retrospective cohort study was conducted. Donor and recipient demographics as well as operative characteristics were collected. Outcomes included 12-month patient and graft survival, length of hospital stay, ITU readmission, rejection episodes, cytomegalovirus viraemia, tacrolimus dosing and associated levels. Data pre-processing was performed using LibreOffice Calc whilst statistical analysis was conducted using the R programming language. A total of 250 liver transplant patients were included; 125 patients transplanted between April 2019 and July 2020 received innovator tacrolimus and 125 patients transplanted between October 2019 and July 2020 received generic tacrolimus. Donor age, sex and CMV status as well as graft type and cold ischaemic times were similar between the cohorts (p=ns). Recipient age, sex, CMV status, disease aetiology, super urgent listing, UKELD, implantation time and intraoperative blood products were comparable (p=ns). Postoperative factors including starting dose of tacrolimus and azathioprine/mycophenolate mofetil use did not demonstrate significant differences. A higher proportion of patients in the innovator cohort had previously been transplanted (innovator 18.3% v generic 7.5%, p=.017) as well as being subjected to ex-vivo normothermic machine perfusion (innovator 21.7% v generic 10.4%, p=.011). Conversely, a higher proportion of patients in the generic cohort were subject to renal sparing protocol (innovator 7.0% v generic 17.2%, p=.025). Patient and graft survival as well as length of hospital stay, rejection episodes, renal function and CMV viraemia were similar between the cohorts (p=ns). There were neither differences in tacrolimus levels on day 3 and day 7 post-transplantation nor at discharge (p=ns). Although the total daily tacrolimus dose at discharge was similar (innovator 8.3 mg/day v generic 9.2 mg/day p=.132), there was a higher daily tacrolimus dose on day 7 post-transplant in the generic cohort (innovator 6.5 mg/day v generic 7.6 mg/day, p=0.018). Clinical outcomes for patients receiving generic tacrolimus in liver transplantation are similar to those receiving innovator tacrolimus. A higher dose of the generic product may be required to achieve clinical equivalence. This could impact on the cost savings traditionally attributed with the use of generic tacrolimus.